2018
DOI: 10.17358/ijbe.4.2.197
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Religiousity, Pricing and Corporate Image on The Attitude and The Intention to Use Sharia Micro Financing

Abstract: The Developing of Micro, Small and Medium Enterprises (MSMEs) in Indonesia could not be separated from the support of banking system in bank credit disbursement to MSMEs sector. Mandiri Sharia Bank (BSM) is one of the sharia banks that had disbursed sharia micro financing (micro credit). The objective of this research was to analyze the influence of religiosity, pricing and corporate image toward the attitude and the intention to use sharia micro financing. This research, hopefully, could give recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 4 publications
1
18
1
3
Order By: Relevance
“…Each person has different religious values. The research of Shabrina (2018) also showed that religiosity has an insignificant influence to intention to use. The result of this research is not in line with that of Firmandhani (2016) stating that religiosity has significant impact on micro community's intention in purchasing sharia insurance.…”
Section: Figure 1 Sem-pls Model Loading Factor Of Variablesmentioning
confidence: 95%
“…Each person has different religious values. The research of Shabrina (2018) also showed that religiosity has an insignificant influence to intention to use. The result of this research is not in line with that of Firmandhani (2016) stating that religiosity has significant impact on micro community's intention in purchasing sharia insurance.…”
Section: Figure 1 Sem-pls Model Loading Factor Of Variablesmentioning
confidence: 95%
“…Rachmawati et al (2018) conducted research on website of Sayur Box to analyze the factors influencing organic fruits and vegetables purchase intention based on WebQual and theory of behaviour and consumer behaviour. The result shows that online purchase intention was affected by attitude and perceived behaviour control (Shabrina et al 2018;Setiawati et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…(terima H8). Hal tersebut sesuai dengan hasil penelitian yang dilakukan olehWeng et al (2018),Shabrina et al (2018) danSetiawati et al (2018), meskipun bertentangan dengan studiNugroho et al (2018).Perceived usefulness secara langsung berpengaruh signifikan terhadap behavioral intention. Semakin banyak manfaat yang didapat oleh nasabah dalam menggunakan internet banking maka akan memengaruhi minat pengguna untuk menggunakan kembali internet banking.…”
unclassified